BATIK PEWARNA ALAM DENGAN TEKHNIK ECOPRINT SEBAGAI POTENSI PENGEMBANGAN WILAYAH INDIKASI GEOGRAFIS - Fitika Andraini; Adi Suliantoro Arikha Saputra (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
Geographical Indication is a legal protection to protect an item as a sign of the area of origin of an item due to several unique factors that are only owned by certain areas. Arrangements in TRIPs are based on the reputation, quality and distinctive characteristics of an area/region. Geographical Indications are a separate intellectual property that is unique because it can only be registered as a joint/communal right. The Indonesian law governing Geographical Indications is placed in one law together with trademarks, namely Law Number 20 of 2016 concerning Marks and Geographical Indications. in terms of product marketing and in terms of supervision. The setting of Geographical Indications must be able to adopt and support local economic development efforts and even be able to compete globally so that what criteria are needed to be granted this right. Criteria if a product can be registered as a Geographical Indication if it meets the objective and subjective requirements. Apart from distinguishing the special aspects of the name of origin of the goods, it must have economic value. This means that the name of origin does not only function as a differentiator, but it must be clear that the place of origin has a great influence on improving the quality of the goods. For example, natural color batik from Asem leaves and Ketapang leaves from the city of Semarang. Batik as an intangible heritage of the Indonesian nation was recognized by UNESCO on October 2, 2009. Batik is basically a technique of decorating textile surfaces by holding back dye, which must receive legal protection. One of the batik techniques instead of using canting is the Ecoprint Technique. As a cultural heritage of the Indonesian nation, especially in the city of Semarang, a sustainability of cultural heritage, especially Batik with natural dyes, is needed which requires government attention by obtaining permanent legal protection. The use of natural coloring from natural materials belonging to certain areas using the Ecoprint Technique can be a potential area for the development of Geographical Indications.